Education for sustainable development in vulnerable contexts: the role of neighborhood and associative movements - De La Rosa Ruiz, Daniel; Gimenez Armentia, Pilar (Frontiers in Education, 2025)
BackgroundIn vulnerable urban contexts, neighborhood and associative movements often emerge as key responses to structural inequalities and social fragmentation. Recent global crises, such as the COVID-19 pandemic, have intensified the need to strengthen community-based responses and promote more inclusive and sustainable forms of development. Within this scenario, Education for Sustainable Development (ESD) has the potential to become a powerful driver of social transformation, particularly when applied from a grassroots, community-based perspective. This study examines the role of grassroots neighborhood initiatives in promoting the core principles of ESD, such as equity, inclusion, and democratic participation.MethodAdopting a socio-educational and participatory approach, this research employed a qualitative methodology based on semi-structured interviews with 40 key actors involved in neighborhood and associative networks. The data were analyzed using the qualitative software Atlas.ti, combining thematic coding with visual tools such as word clouds and semantic network analysis to identify dominant patterns and relationships. The study focused on understanding how fundamental principles of ESD—including equity, inclusion, co-responsibility, and respect for diversity—are integrated into the practices and discourses of these community initiatives.ResultsThe analysis reveals strong patterns of cooperation, mutual support, and democratic participation within neighborhood and associative movements. These networks serve not only as mechanisms to meet urgent material needs but also as spaces of informal education and civic empowerment. The incorporation of ESD principles into community dynamics has contributed to the strengthening of the social fabric and to the emergence of new forms of collective agency. In particular, the findings highlight how community-led practices of inclusion and co-responsibility foster critical reflection and shared decision-making, reinforcing social cohesion and contributing to the construction of more just and sustainable neighborhoods.ConclusionThe study provides evidence that Education for Sustainable Development, when applied from a bottom-up and participatory perspective, plays a strategic role in promoting social transformation in vulnerable settings. By supporting neighborhood and associative movements, ESD contributes not only to addressing immediate social needs, but also to fostering long-term processes of inclusion, empowerment, and sustainability. These findings suggest that ESD should be more widely recognized as a key lever for strengthening community resilience and advancing the Sustainable Development Goals (SDGs) at the local level.